Asosiasi Pola Asuh Gizi dan Kesehatan dengan Kasus Balita Stunting di Area Kerja Puskesmas Cikulur, Banten - Mardhiah, Himmatun; Aulia Rahma, Fadilah; Apriningsih, Apriningsih (LPPM Hang Tuah Pekanbaru, 2024)
Background: Being too short for their age is a symptom of stunting, which is the inability to thrive as a result of chronic malnutrition beginning at birth. The prevalence of Stunting in Banten Province is 29.6%. Many studies have examined the factors that influence the incidence of stunting in infants, but a few articles have focused on nutritional and healthcare parenting. Objectives: This research aims to determine the association of nutritional, health, and psychosocial parenting with Stunting cases among children in Cikulur Primary Health Center’s working area.Methods: This research uses a cross-sectional study design with a quantitative approach whose analysis is done using the Chi-square test. The instrument used in measuring the independent variable was a questionnaire while the dependent variable used anthropometric measurements and growth charts. The study was conducted in June 2020 with a sample of 137 mothers with children under five. Result: This research obtained that the proportion of stunting children in this study was 51.8%. There is a significant association between nutrition parenting with Stunting (p-value: 0.015, POR: 0.399 CI%: 0.199 – 0,799), and healthcare patterns parenting (p-value of 0.022 and POR: 0.425, CI: 0.214 - 0.843). There is no association between psychosocial parenting with Stunting. Conclusion: Nutritional parenting and healthcare parenting are associated with children’s stunting cases. Mothers are supposed to support their children under five in their growth and development, as well as give them a healthy diet and healthcare attention.